CSR disclosure — legitimacy dan perubahan retorika - Imam Wahyudi (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2017)
This study decribes and analyzes the rhetorical changes of CSR disclosures of PT Aneka Tambang which relates to the company’s environmental conducts in response to institutional pressures.Using a case study approach – the data for this study based on the sustainability reports published by the company from 2006 -2015. Interpretive textual analysis is exploited by focusing on the use of rhetoric and rhetorical arguments through researcher’s subjective understanding – subjective sense making. The development of the disclosures for the period studied is contrasted with institutional pressures – domestic and international – by exploiting new institutional theory. The results show that for the period of ten years, the company’s disclosures can be categorised into three periods – reducing environmental harm, awareness in preserving environment, and environmental management excellence. In order to gain social legitimacy, institutional pressures from external parties influenced the way how the company adjusted its contents of disclosures.